Which coping strategies moderate the depression-suicide ideation link in Black college students? A psychometric investigation. (July 2022) - Goodwill, Janelle R.
Highlights: The factor structure for the Brief COPE Inventory derived from this sample of Black students did not align with the factor structure presented in the original validation of this scale. The PHQ-8 measure of depressive symptoms yielded the same factor structure presented in the original validation of this scale. Self-blame/behavioral disengagement coping strategies were positively associated with past-year suicide ideation. Religious coping strategies were negatively associated with past-year suicide ideation. Social support, self-blame, and religious coping strategies moderated the relation between depressive symptoms and past-year suicide ideation. Abstract: The current study analyzed data from 413 Black college students who participated in the 2015–2016 Healthy Minds Study to identify which specific coping strategies moderate the relation between depressive symptoms and past-year suicide ideation. Exploratory and confirmatory factor analysis techniques were used to first examine dimensionality of the Brief COPE Inventory and depression measures. Findings from this sequential process revealed that the factor structure for the Brief COPE Inventory derived from this sample of Black students did not align with the factor structure generated in the original validation. Self-blame/behavioral disengagement coping strategies were positively associated with past-year suicide ideation, though religious coping strategies were negatively associated with past-year suicide ideation. Moreover, social support, self-blame/behavioral disengagement, and religious coping strategies each moderated the relation between depression and suicide ideation. Identifying specific coping strategies that either exacerbate or mitigate suicide risk is necessary when working to build a proactive culture of prevention.